Acacia : finding a cure for information silos disorder - Granados, Nelson F.; Shanahan, Doreen E. ([London] : SAGE, 2016)
Acacia's founder and CEO, Dan Hyun, had been acting as a 'one-man IT department' for the company since its inception in 1990. Early on, the IT infrastructure of the company was quite simple. But as the business grew, Hyun purchased several servers and eventually an enterprise software package. Needing a system to manage the company's growing production requirements and inventory, Hyun created a database on a computer in the company's warehouse using Access. He later expanded the Access database to house sales information. By 2013, the patchwork of process, systems and software lay at the root of some operational problems, including order delays, stock-outs, and order duplications. As a small company, with limited cash flow, such mistakes could be disastrous. This case study examines this topic.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Information technology -- Management -- Case studies; Information storage and retrieval systems -- Business -- Case studies; Management information systems -- Case studies